Sustainable Happiness : Live Simply, Live Well, Make a Difference. - Van Gelder, Sarah (Berrett-Koehler Publishers, 2015)
We're bombarded by messages telling us that more, bigger, and better things are the keys to happiness-but after we pile up the stuff and pile on the hours, we end up exhausted and broke on a planet full of trash. Sarah van Gelder and her colleagues at YES! Magazine have been exploring the meaning of real happiness for eighteen years. In this much-needed volume, they marshal fascinating research, in-depth essays, and compelling personal stories that lead to a life-altering conclusion: what makes us truly happy are the depth of our relationships, the quality of our communities, the contribution.